Caracterização biológica e morfológica de duas cepas de Trypanosoma cruzi isoladas de espécimes de Triatoma sherlocki coletadas em Santo Inácio, BA - Castilho, Jéssica Sacchi [UNESP] (2017)
Latin America is the area where the largest number of people with Chagas' disease is found. Estimates indicate that are between 6-8 million infected people in the world. But in recent decades, with the increasing of population mobility between Latin America and other countries, chagasic patients can be found in the United States, Canada, European and Eastern Pacific countries. Trypanosoma cruzi, the etiologic agent of Chagas' disease, presents high variability it can be differentiated by biological, biochemical, immunological and genetic markers. Two strains of T. cruzi (Tsh1 and Tsh7) studied were isolated from the laboratory of Parasitology of the Faculty of Pharmaceutical Sciences/UNESP/Araraquara, from two specimens of Triatoma sherlocki collected in Santo Inácio, Bahia. The strains were maintained in LIT (Liver Infusion Tryptose) culture medium, where the growth kinetics were evaluated, and from the forms obtained in culture a parasitemic curve was developed in Swiss mice, determining a pre-patent period, parasitemic peak, mortality and disappearance of circulating forms in the peripheral blood of the mice in order to establish the pattern of infection. These same blood trypomastigote forms were evaluated microscopically, where the morphological characteristics of the strains were determined. Thus, T. cruzi strains isolated from specimens collected in Santo Inácio showed low virulence and low parasitemia when compared to the reference strain, Y. Molecular and biological studies are under development, in order to increase the knowledge about the strains Tsh1 and Tsh7 from T. cruzi. No articles has been found on isolation and characterization...